Beyond the physical: Integrating qualitative elements in elderly care homes design guidelines (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Residential care facilities (RCFs) face a critical design paradox as the world's population ages: regulatory frameworks heavily prioritize physical safety while largely neglecting the psychosocial and experiential needs of elderly people. By emphasizing risk mitigation, current guidelines often produce environments that favor survival over dignity and meaning. Using a mixed-methods approach that combines qualitative coding and computational text mining (Voyant Tools), this study analyzes 22 international design guidelines and reveals a pronounced lexical bias, in which “safety” consistently outweighs concepts such as identity, social interaction, autonomy, and cognitive stimulation. To address this structural gap, this study introduces six evidence-based Qualitative Design Parameters (QDPs) an interdisciplinary framework integrating environmental psychology, gerontology, and architectural theory. These parameters reposition care settings as places that affirm personhood beyond risk containment: autonomy, sensory richness, narrative continuity, social vitality, environmental familiarity, and biophilic engagement. Findings highlight that despite strong evidence linking spatial design to mental health, existing standards rarely address loneliness, cognitive decline, or agency loss. The proposed framework therefore advances a paradigm shift by completing safety compliance with qualitative measures of emotional well-being, dignity and lived experience. This work offers a roadmap for transforming RCF guidelines into more holistic and human-centered standards.